When a Dead Patient Is Not Really Dead: Lazarus Phenomenon - Munish Sharma; Megha Chandna; Thang Nguyen; Abhay Vakil; Rene Franco; Iqbal Ratnani; Joseph Varon; Salim Surani (Case Reports in Critical Care)
Lazarus phenomenon refers to autoresuscitation of a patient declared dead after cessation of cardiopulmonary resuscitation (CPR). The Lazarus phenomenon is rarely encountered and pathophysiology is not very well understood, but physicians need to be aware of this phenomenon. It is prudent that a physician leading a CPR effort waits for some time and monitors the patient further using blood pressure and electrocardiogram before confirming that a patient is actually dead.